Redução da proteína em dietas para a tilápia-do-Nilo pela suplementação de aminoácidos com base no conceito de proteína ideal - Righetti, José Sérgio (2009)
This work was carried undertaken out to evaluate the effects of protein reduction in Nile tilapia diets by amino acid supplementation based on the ideal protein concept on performance, digestibility and diameter of muscle fiber. One-hundred and sixty fish (105.7 ± 2.5 g) were distributed in 16 tanks and fed with diets containing 26,74; 25,82; 23,09 or 22,16% of digestible protein, during 110 days. Crystalline amino acids (L-lysine, DL-methionine, L-threonine and L-arginine) were added to keep amino acid levels according to the ideal protein profile to simulate amino acid levels of the reference diet. No effects of the dietary crude protein levels on daily weight gain, hepatosomatic index, visceral fat, fillet yield, carcass humidity, protein and ash, fillet ash, survival, white muscle fiber diameter and calcium availability were observed. A linear decrease on apparent digestibility coefficients on gross energy, crude protein, ether extract and phosphorus was observed according to protein levels reduction. A quadratic effect was observed on feed conversion ratio, protein efficiency ratio, nitrogen retention, nitrogen excretion, fillet humidity, carcass and fillet fat and fillet protein, in which the best-fit responses were obtained with 24.53, 24.25, 24.04, 25.15, 24.67, 24.14, 24.34, 25.11% of digestible protein, respectively. It was concluded that is possible to reduce the dietary protein level from 26.74 to 24.53% for Nile tilapia phase of 100 to 500g, to obtain the best results on feed conversion ratio, nitrogen utilization and body and fillet chemical composition, without negative effects on all parameters of performance.